Cases of (w) and (y) letter as the second radical of roots: Weakening (ilāl) as phonetic phenomena in Al-Shafia book by Ibn-Al-hajeb (modern phonetic study) - Hameed Mohsin Ali Al-Ta'ee, Hasan (International Journal of Psychosocial Rehabilitation, 2020)
The present study focuses on the caused phenomenon accompanied to the causing concepts in the linguistic structures by the linguist considered his work (Al –Shafieah). This study is under name (Al waw and al Yha .The study considers the causing procedures for this topic by previous linguists and the followers to Ibn-Al hajib for generalizing. To highlight on these opinions by linguists and compered these opinions with the modern linguists and their procedures for they deal with this point according to Modern Phonetics principles which stretch his arms to inter for finding the scientific causes and justifications to the phenomena in Arabic linguistic structures through consider segmental analysis in drawing the structural pattern and consider the phonetic rules such as: Differences and similarities rules. These rules play role in showing the clear view to the phonetic justifications to arrive to the final views of structures. The significance of the research lies in present the morphological matter from phonetic point of view.